The Effects of Sn-Doping on a-Fe2O3 Nanostructures Properties - R.W. Ahmad, W; H. Mamat, M; S. Zoolfakar, A; Khusaimi, Z; M. Yusof, M; S. Ismail, A; A. Saidi, S; Rusop, M (International Journal of Engineering and Technology, 2018)
In this study, undoped and Sn-doped hematite (Î±-Fe2O3) nanostructures with variation of Sn (0.5, 1, 2, 3 at. %) were deposited on fluorine doped tin oxide (FTO) coated glass substrate using sonicated immersion method. The effect of Sn-dopant on structural and crystallinity properties were investigated by characterizing FESEM and XRD respectively, while the optical properties were measured by UV-Vis-NIR spectrometer. The surface morphologies from FESEM have shown that the hematite nanostructures were grown uniformly in all samples. However, as the dopant atomic percentage increases, the amount of hematite nanostructure being grown on the FTO decreases. Results demonstrated that the amount of Sn-doping was undoubtedly influence the structural, optical and electrical properties of hematite nanostructures.Â Â